Circadian Rhythm and Stress Response in Droppings of Serinus canaria - Maura Turriani; Nicola Bernabò; Barbara Barboni; Gianluca Todisco; Luigi Montini; Paolo Berardinelli (Veterinary Medicine International)
Serinus canaria is a widespread domestic ornamental songbird, whose limited knowledge of biology make compelling studies aimed to monitor stress. Here, a commercial enzyme immunoassay was adopted to measure immunoreactive corticosterone (CORT) in single Serinus canaria dropping sample, to monitor the daily fecal excretion of CORT in birds bred singly or in-group and to detect the effect promoted by aviary or small transport cage restraint. A robust daily rhythm of CORT was recorded in animals held on short-day light cycle, independent of bred conditions (single or group), which persisted when space availability was modified in single bred animal (transfer in aviary and transport cages). By contrast, a significant change in CORT excretion was recorded when group bred animals are restrained in a smaller cage. The daily rhythm in CORT excretion in response to manipulation showed the greatest response at the beginning of the light period, followed by the absence of the peak usually recorded at the end of the dark phase. These data indicated that EIA could be used as a reliable noninvasive approach to monitor the stress induced by restraint conditions in Serinus canaria.